Anti-neutrophil cytoplasmic antibodies negative eosinophilic granulomatous polyangiitis glomerulonephritis in children - A diagnostic dilemma - Sharma, Shobha; Kalra, Suprita; Sinha, Aditi; Bagga, Arvind (Indian Journal of Child Health, 2018)
Anti-neutrophil cytoplasmic antibodies (ANCA) associated vasculitis (AAV) refers to small-to-medium vessel vasculitis with multisystemic involvement and is characterized by the presence of ANCA to specifically either proteinase-3 (PR3) or myeloperoxidase (MPO). Eosinophilic granulomatous polyangiitis earlier called as Churg-Strauss vasculitis is a clinicopathological variant of AAV or AAV with granulomatous necrotizing small vessel vasculitis primarily affecting individuals with severe asthma or allergies and rarely reported in the pediatric population. We report a 9-year-old child with pauci-immune crescentic eosinophilic granulomatous glomerulonephritis with heavy eosinophilic infiltration of skin and subcutaneous tissue and negative ANCA. Although he had a recurrent history of cough, there was no history of use of oral or inhalational bronchodilator therapy indicating asthma and no history suggestive history of allergy. He showed significant and rapid clinical as well as biochemical improvement on aggressive immunosuppressive therapy along with plasma exchanges and is under regular follow-up. Diagnosing Eosinophilic granulomatous Polyangiitis glomerulonephritis in children is difficult due to a varied clinical presentation at onset which may evolve over a period of time and due to lack of specific diagnostic tests. High index of suspicion is the key to early diagnosis and successful management.